Socialno-ekonomske in okoljske značilnosti regionalnega razvoja Slovenije po letu 2010 - Vintar Mally, Katja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2021)
The primary goals of regional policy in Slovenia are reducing regional development disparities and ensuring balanced development based on the principles of sustainable development. This article examines the performance of Slovenian regions in achieving these goals in the socioeconomic and environmental fields after 2010. For this purpose, four synthetic indicators (gross domestic product per capita, ecological footprint per capita, development risk index and indicator of sustainable regional development) and 32 separate economic, social and environmental indicators, which are also included in the calculation of the indicator of sustainable regional development, were examined. Most of the economic and social indicators indicate progress towards the strategic development goals, while most of the environmental indicators show a shift away from them.
Keywords: development disparities; indicators; kazalniki; razvojne razlike; Slovenia; Slovenija; statistical regions; statistične regije; sustainable development; trajnostni razvoj